LAKON SEMAR MBANGUN KAHYANGAN DALAM PERSPEKTIF AKSIOLOGIS MAX SCHELER (RELEVANSINYA TERHADAP PEMBANGUNAN MENTAL MASYARAKAT) - Rima Ronika (Refleksi: Jurnal Filsafat dan Pemikiran Keislaman, 2016)
Wayangas high culture that rich of symbols contains a lot of values that could be a guide and direction to common people in Indonesia. Lakon Semar Mbangun Kahyangan is one of lakoncarangan  that shows moral values to its audiences. Through theory of value from Max Scheler, lakon Semar Mbangun Kahyangan gets its value's meaningnot from its symbols, but from its phenomena that arisen. Max Scheler believes that symbol indeed hides its true meaning, therefore the meaning will be found by inspect to the existence of its reality. Arjuna, Sri Kresna, and Bathara Guru in reality could do badness. This is, of course, contradict with meaning of the symbols that contained in it, i.e. goodness. Therefore, the value meaning in wayang could not only be done by look as symbolic, however to inspect from the existence of its reality. As a result, the meaning will be revealed, even the value agents are changed, that will not change the goodness meaning that contained in the value agent.